Smart biopolymers and their applications - Abu, Tariq; Showkat, Ahmad Bhawani; Khalid M., Alotaibic; Abdul, Moheman (Woodhead Publishing, 2021)
Polymers have a sacred space in science. It is a well-known fact that due to some unique and specific properties polymers are used in a wide range of applications. Among them smart biopolymers have gained attention of researchers worldwide due to their unique properties such as biodegradability, biocompatibility, inexpensiveness, and renewability. Furthermore, these smart biopolymers show a characteristic property of responsiveness to stimuli such as temperature, pH, magnetic and electrical field, chemical, mechanical stress, and light. Consequently, succeeding chapter will briefly shed light about such smart biopolymers, their classification, and applications. Special attention is laid on the potential applicability of such smart biopolymers in the field of drug delivery, tissue engineering scaffolds, bioseparation, biotechnology, other medicinal fields, etc. The versatility and unique potential of these smart polymers make them one of the important parts of science, specifically medicine and drug delivery.